2014
DOI: 10.1007/s00542-014-2349-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a clamped–clamped microbeam resonator considering fabrication imperfections

Abstract: We present an investigation into the static and dynamic behavior of an electrostatically actuated clamped-clamped polysilicon microbeam resonator accounting for its fabrication imperfections, which are commonly encountered in similar microstructures. These are mainly because of the initial deformation of the beam due to stress gradient and its flexible anchors. First, we show experimental data of the microbeam when driven electrically by varying the amplitude and frequency of the voltage loads. The results rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
(39 reference statements)
1
9
0
Order By: Relevance
“…This implies that this is a super harmonic resonance of order three. The phase portrait in Figure 6d shows two loops at 35 kHz, which also confirms a super harmonic resonance of order two [48].…”
Section: The Effect Of DC and Ac On The Super Harmonic Resonancessupporting
confidence: 59%
See 1 more Smart Citation
“…This implies that this is a super harmonic resonance of order three. The phase portrait in Figure 6d shows two loops at 35 kHz, which also confirms a super harmonic resonance of order two [48].…”
Section: The Effect Of DC and Ac On The Super Harmonic Resonancessupporting
confidence: 59%
“…The nonlinear equation governing the transverse motion w(x,t) of the arch microbeam shown in figure 1 [38][39][40][41][42][43][47][48][49] is as following…”
Section: Problem Formulationmentioning
confidence: 99%
“…Next, we prove the inherent quadratic nonlinearity of the arch regardless of its actuation method (i.e., whether there is a DC electrostatic force or not), which shows a softening nonlinear response. The nonlinear equation governing the transverse motion w ( x , t ) of the arch beam based on no axial inertia can be written as [ 41 , 42 , 43 , 44 , 45 ]: where x is the spatial position, t is time, and w 0 is the initial curvature of the arch. The arch has a Young’s modulus E , a material density ρ, and is assumed to have a rectangular cross-sectional area A and a moment of inertia I .…”
Section: Softening Nonlinearity In Arch Microbeammentioning
confidence: 99%
“…Here, we exploit the softening behavior in an arch-shaped beam for memory application. Unlike electrostatically actuated cantilever microbeams, where the softening nonlinear behavior is solely caused by the DC bias voltage, an arch shaped clamped–clamped microbeam shows softening nonlinearity due to its initial curvature [ 41 , 42 , 43 , 44 , 45 , 46 ]. Hence, the nonlinearity in this case is mainly of mechanical origin, and thus is almost independent of the DC bias (does not put any restriction on the amount of bias needed to trigger the nonlinearity), and can even be actuated using other methods, such as piezoelectric.…”
Section: Introductionmentioning
confidence: 99%
“…Although the model predicted the resonator behavior at low amplitudes, it failed to capture the response at high amplitude of vibration. In [32,33], it was shown that the shooting method is more robust and can predict the stable and unstable periodic solution accurately compared to Runge-Kutta, which depends on robustness and the size of the basin of attraction.…”
Section: Introductionmentioning
confidence: 99%